The Utilisation of Coconut Water Waste into Nanocellulose and Potential Synergistic Effect of Asthma Plant (Euphorbia hirta L.) Extract as an Antibacterial Agent - Barus, Lydia Br; Manihuruk, Fani Nuryana; Sari, Mesi Puspita; Simanjuntak, Helen Anjelina; Ginting, Junius Gian; Purba, Hermawan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Skin infections contribute to one of the most significant global health issues. Acne, blisters, and abscesses are examples of skin infections that can be induced by Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Treatment can be attempted through the development of nanotechnology in the form of nanocellulose. Nanocellulose, an organic substance, can be produced through the conversionÂ of coconut water waste and Acetobacter xylinum bacteria. Future applications of nanocellulose formulated with a blend of extracts derived from natural sources, including Patikan Kebo (Euphorbia hirta L.), are anticipated to include the treatment of wound dressings (patches). Determining the antibacterial potential of nanocellulose was the objective of this study. The experimental research technique is implemented in phases. The extraction process was conducted by means of maceration, while the parallel streak method was utilized for antibacterial testing. The findings of the study indicated that the mean zone of inhibition for each treatment variable was as follows: 0 mm, 15.1 mm, 23.53 mm, and 23.06 mm for nanocellulose (serving as the negative control), nanocellulose and 0.5% extract, 1% extract, 1.5% extract, and clindamycin, respectively. Conclusion: Antibacterial activity was observed in nanocellulose extracts containing 1% and 1.5%